Analisis Pengaruh Perputaran Persediaan, Perputaran Kas dan Perputaran Piutang terhadap Profitabilitas pada Perusahaan Rokok yang terdaftar di BEI Periode 2018-2023 - Mustafa, Syamfiere Rangga (Universitas Islam Kadiri, 2025)
This study aims to evaluate the impact of inventory turnover, cash turnover, and accounts receivable turnover on profitability in cigarette companies listed on the IDX during the 2018-2023 period. This study uses a quantitative descriptive approach. The sample consists of quarterly financial statements of 5 cigarette companies listed on the Indonesia Stock Exchange, with a total of 120 observations. Data were analyzed using multiple linear regression through the EViews 12 application. The research findings indicate that inventory turnover, cash turnover, and accounts receivable turnover all have a significant positive effect on profitability.